Aerogels as porous structures for food applications: Smart ingredients and novel packaging materials. (April 2021) - Manzocco, Lara; Mikkonen, Kirsi S.; García-González, Carlos A.
Graphical abstract: Highlights: Aerogels are nanostructured materials with low bulk density and open porosity. Food-grade aerogels are prepared from several bio-based materials. Aerogels can be loaded to obtain delivery systems for food and packaging applications. Aerogels can turn into oleogels by oil absorption within the pores. Abstract: Aerogels are nanostructured materials with low density, high surface area (>150 m 2 /g) and open porosity (typically 95–99.99 %). They are obtained by solvent removal from gels while preserving network structure. Hydrogels, organogels and even tissues can be optimal sources of aerogels with limitless customization of format and texture. Aerogels might be used for a range of advanced food applications: from smart ingredients controlling nutrient release to delivery systems for active compounds; from fat substitutes to novel biodegradable and intelligent food packaging materials. This review article summarizes recent developments of aerogels in food applications, analyzing research challenges and prospecting future markets.